Increasing Teacher Competency using the contextual inquiry Learning Model through In-House Training at SD Negeri 1 Giripurwo Kapanewon Girimulyo Kulon Progo Regency Academic Year 2022/2023 - Yunarti Farida, Endang (IJCER (International Journal of Chemistry Education Research), 2024)
This research aims to determine teachers' activities and abilities in implementing the Contextual Inquiry Learning, as well as researchers' abilities in managing IHT. School Action Research was carried out at SD Negeri 1 Giripurwo Kapanewon Girimuyo Kulon Progo Regency for the 2022-2023 Academic Year in three cycles consisting of 2 meetings in each cycle, the procedures in this research include planning, implementation/action, observation and reflection . The subjects of this research were 8 people consisting of 6 class teachers and 2 subject teachers. Qualitative data was collected in the form of active observations and the application of the "Contextual Inquiry Learning" learning model, and the researcher's assessment sheet for managing IHT. The research results relate to participant activity, the application of the "Contextual Inquiry Learning" learning model, as well as the management of IHT by researchers. The results of the activities of the first cycle participants at the 1st meeting obtained an average score of 2.56 with a percentage of 79.31%, at the 2nd meeting the average score was 3.40 with a percentage of 85.07%. Furthermore, the results of cycle II of the 1st meeting averaged a score of 3.63 with a percentage of 90.63%, at the 2nd meeting the average score was 3.81 with a percentage of 95.14%. Then, in the application of the learning model for cycles I and II, namely 1. Preparation of syntax/phases, an average score of 91.41% was obtained; Preparation of learning model steps had an average score of 91.15%, 2. Preparation of lesson plans was obtained based on an average of 91.96%, and 3. Teaching practice was 91.25%, while in the IHT Management cycle I, the 1st meeting was obtained an average -average score 3.40 with a percentage of 84.38%, at the 2nd meeting an average score of 3.60 was obtained with a percentage of 89.38%. Next, cycle II, 1st meeting. average score 3.73; percentage 92.81%; Following is the 2nd meeting; average score 3.81; percentage 95.31%; The results of the research concluded that each meeting in cycle I and cycle II had achieved improvement and had met the research success indicator of 85%.